Analysis of Religiosity and Halal Labels Towards Purchasing Decision on Cosmetic Products (Study on Regular Female Student of The University of Darussalam Gontor) - Zulfatus Sa'diah; Milenia Ayu Saraswati; May Shinta Retnowati (JES (Jurnal Ekonomi Syariah), 2022)
This research aims at analyzing religiosity and halal labels toward purchasing decision's regular female students of University of Darussalam Gontor on a cosmetic product. The study uses quantitative methods with an explanatory approach. Then data analysis techniques using Structural Equation Modelling (SEM) is Partial Least Squares (PLS) with the help of Smart PLS version 3.2.9. to answer hypotheses. The first stage in the study was testing the validity of each variable question with its reliabilities. The second one verifying the combination between religiosity and halal labels toward purchase decisions on cosmetic products among regular female students of University of Darussalam Gontor. The results showed that halal labels influenced purchasing decisions by 68%, while the remaining 32% were influenced by another exogenous outside of the studied variables. The religiosity partially has a positive but insignificant effect on purchasing decisions. Whereas the halal labels partially have a positive and significant effect on purchasing decisions.